Cardiovascular events and risk in patients with systemic lupus erythematosus: Systematic literature review and meta-analysis. (March 2023) - Bello, Natalia; Meyers, Kristin J; Workman, Jennifer; Hartley, Louise; McMahon, Maureen
Background: Systemic lupus erythematosus (SLE) is an autoimmune disease that typically affects women aged 16–55 years. Cardiovascular disease (CVD) is a well-recognized complication of SLE. This systematic literature review and meta-analysis evaluated the relative risk (RR; compared with non-SLE controls), absolute risk (AR; as incidence proportion, n/N), and incidence rate (IR) of CVD events (including stroke, myocardial infarction [MI], and CVD [composite or undefined]) in adult patients with SLE. The RR of CV risk factors (including hypertension, diabetes, and metabolic syndrome [MetS]) was also examined. Methods: PubMed and Embase were searched on September 10, 2020. Observational studies published between January 2010 and September 2020 that reported RR, AR, and/or IR of CVD events, or RR of CV risk factors, were eligible. Pooled risk estimates were calculated using a random-effects model. Results: Forty-six studies (16 cross-sectional, 15 retrospective cohort, 14 prospective cohort, and 1 case–control) were included in meta-analyses. Most studies were considered high quality (Critical Appraisal Skills Programme checklists). Compared with adults without SLE, patients with SLE had statistically significantly higher RRs (95% CIs) of stroke (2.51 [2.03–3.10]; 12 studies), MI (2.92 [2.45–3.48]; 11 studies), CVD (2.24 [1.94–2.59]; 8 studies), and hypertension (2.70 [1.48–4.92]; 7 studies). RRs of diabetes (1.24 [0.78–1.96]; 3 studies) and MetS (1.49 [0.95–2.33]; 7 studies) were elevated but not significant. RRs of stroke and MI were generally higher in younger versus older patients with SLE. In patients with SLE, the pooled estimate of AR (95% CI) was 0.03 (0.02–0.05), 0.01 (0.00–0.02), and 0.06 (0.03–0.10) for stroke (7 studies), MI (6 studies), and CVD (8 studies), respectively. The pooled estimate of IR per 1000 person-years (95% CI) was 4.72 (3.35–6.32), 2.81 (1.61–4.32), and 11.21 (8.48–14.32) for stroke (10 studies), MI (6 studies), and CVD (8 studies), respectively. Although heterogeneity (based on I 2 value) was high in most analyses, sensitivity analyses confirmed the robustness of the pooled estimates. Conclusions: This meta-analysis found an increased risk of stroke, MI, CVD, and hypertension in patients with SLE compared with the general population, despite substantial heterogeneity across the included studies.